Production, characterization, and antigen specificity of recombinant 62‐71‐3, a candidate monoclonal antibody for rabies prophylaxis in humans. Issue 5 (31st January 2013) - Both, Leonard; van Dolleweerd, Craig; Wright, Edward; Banyard, Ashley C.; Bulmer‐Thomas, Bianca; Selden, David; Altmann, Friedrich; Fooks, Anthony R.; Ma, Julian K.‐C.
Abstract : Rabies kills many people throughout the developing world every year. The murine monoclonal antibody (mAb) 62‐71‐3 was recently identified for its potential application in rabies postexposure prophylaxis (PEP). The purpose here was to establish a plant‐based production system for a chimeric mouse‐human version of mAb 62‐71‐3, to characterize the recombinant antibody and investigate at a molecular level its interaction with rabies virus glycoprotein. Chimeric 62‐71‐3 was successfully expressed in Nicotiana benthamiana. Glycosylation was analyzed by mass spectroscopy; functionality was confirmed by antigen ELISA, as well as rabies and pseudotype virus neutralization. Epitope characterization was performed using pseudotype virus expressing mutagenized rabies glycoproteins. Purified mAb demonstrated potent viral neutralization at 500 IU/mg. A critical role for antigenic site I of the glycoprotein, as well as for two specific amino acid residues (K226 and G229) within site I, was identified with regard to mAb 62‐71‐3 neutralization. Pseudotype viruses expressing glycoprotein from lyssaviruses known not to be neutralized by this antibody were the controls. The results provide the molecular rationale for developing 62‐71‐3 mAb for rabies PEP; they also establish the basis for developing an inexpensive plant‐based antibody product to benefit low‐income families in developing countries.—Both, L., van Dolleweerd, C., Wright, E., Banyard, A. C., Bulmer‐Thomas, B., Selden, D., Altmann, F., Fooks, A. R., Ma, J. K.‐C. Production, characterization, and antigen specificity of recombinant 62‐71‐3, a candidate monoclonal antibody for rabies prophylaxis in humans. FASEB J. 27, 2055–2065 (2013). www.fasebj.org